The first extinct species of Monolepta Chevrolat (Coleoptera: Chrysomelidae: Galerucinae) from Bitterfeld amber, described using X-ray micro-computed tomography - Bukejs, Andris; Bezděk, Jan; Kairišs, Kristaps; Alekseev, Vitalii Igorevich (Zootaxa, 2021)
Based on a well preserved female specimen from Bitterfeld amber, Monolepta rappsilberi sp. nov. is described and illustrated using X-ray micro-computed tomography (μCT). It is the second reported member of Chrysomelidae from this fossil resin and the first described fossil Monolepta representative. The fossil species represents a lineage that is extinct in Recent Europe. A longitudinal carina on abdominal ventrite 5 of the female is a unique character for the subfamily Galerucinae.